2009
DOI: 10.12973/ejmste/75284
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Teaching Anxiety about Mathematics and Their Learning Styles

Abstract: The purpose of this study was to investigate the differences in the teaching anxiety of preservice teachers in mathematics according to their learning style preferences. There were a total of 506 pre-service teachers involved in this study. Of the total, 205 were pre-service elementary school teachers, 173 were pre-service elementary mathematics teachers, and 128 were pre-service secondary mathematics teachers. In the collection of the data, the researcher employed two types of instruments: the Learning Style … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
2
39

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 25 publications
1
75
2
39
Order By: Relevance
“…Besides the mathematical values of pre-service teachers in mathematics education, their teaching anxiety in mathematics is also an important issue under study (Peker, 2006(Peker, , 2008(Peker, , 2009a(Peker, , 2009b(Peker, , 2009cPeker & Halat, 2008, 2009Peker, Halat & Mirasyedioğlu, 2010). Teaching anxiety is defined as the anxiety experienced in relation with the teaching process comprising the preparation and implementation of classroom activities (Gardner & Leak, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the mathematical values of pre-service teachers in mathematics education, their teaching anxiety in mathematics is also an important issue under study (Peker, 2006(Peker, , 2008(Peker, , 2009a(Peker, , 2009b(Peker, , 2009cPeker & Halat, 2008, 2009Peker, Halat & Mirasyedioğlu, 2010). Teaching anxiety is defined as the anxiety experienced in relation with the teaching process comprising the preparation and implementation of classroom activities (Gardner & Leak, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Levine (1996) has stated that high levels of mathematics teaching anxiety in pre-service teachers are related to insufficient math knowl-edge and bad mathematics learning experiences in the past. At the same time, in other research carried out, it was established that the teaching anxieties of pre-service teachers was dependent on the concrete materials they required in teaching mathematics, that is, the more concrete materials needed, the higher teaching anxiety of the pre-service teachers (Peker, 2008), that the teaching anxieties of pre-service teachers in mathematics was influenced by the teaching methods applied in lectures attended in university (Peker, 2009a(Peker, , 2009cPeker & Halat, 2009), that teaching anxiety differed according to the learning styles of pre-service teachers (Peker, 2009b), and that there is no statistically significant difference according to gender in the mathematics teaching anxieties of pre-service primary school teachers (Peker & Halat, 2008) and in teaching anxieties of pre-service mathematics teachers (Peker, Halat & Mirasyedioğlu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Peker (2008) found that when the need for finding concrete examples for pre-service teachers' teaching is increasing, the pre service teachers' levels of anxiety about mathematics teaching are also increasing. As a result of the study by Peker (2009b), it was determined that the use of expanded microteaching reduced preservice teachers' teaching anxiety about mathematics. Uusimaki and Nason (2004) reported that pre-service teachers' negative beliefs and anxiety about mathematics have a powerful impact on the practice of teaching.…”
mentioning
confidence: 99%
“…Bunun için önce, matematik öğretmen ve öğretmen adaylarının kendi öğrenme stillerini ve özelliklerini kapsamlı olarak bilmeli ve tanımalıdır. Matematik öğretmen adaylarının öğrenme stillerinin belirlenmesine ve öğrenme stiline dayalı öğrenme süreçlerinin incelenmesine yönelik araştırmaların (Ali & Kor, 2007;Elçi, 2008;Ertekin, Dilmaç & Yazıcı, 2009;Fer, 2003;Küçükkaragöz, et al, 2009;Orhun, 2007;Peker, Mirasyedioğlu & Aydın, 2004;Peker, 2009;Perry & Ball, 2004) yapıldığı bilinmektedir. Ancak, öğrenme stili modellerinin temellerindeki farklılıklar ve ölçme araçlarının yapısı ve belli değerlendirmeler nedeniyle öğrenme stillerinin esnek yapısı tam olarak görülememektedir.…”
Section: öğRenme Stilleriunclassified